Kontribusi Intellectual Capital dan Loan to Deposit Ratio terhadap kinerja keuangan Bank Umum Milik Swasta Devisa - Rika Aprilyani (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
The population and data source in this study focuses on the financial sector which is one of the sectors contained in the service industry, namely the banking sub-sector company of the private public Bank of foreign exchange. This research is based on an increase in total assets each year during the year 2014-2018 but the profit generated is volatile. The population of the company's financial report BUMS Devisa listed on the Indonesia Stock Exchange in 2014-2018 with 20 companies. The research methods used are descriptive statistics and analysis of the data regression panel of common effect models. This research aims to analyze how the influence of Value Added Capital Employee (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) and Loan to Deposit Ratio (LDR) against Return on Assets (ROA) both simultaneously or partially. The results of the study showed that the variables of VACA, VAHU, STVA, and LDR simultaneously significantly affect ROA with a probability value of 0.00000. Partials of VACA, VAHU and LDR variables have no effect on ROA. STVA has a positive effect on ROA.